Scoping Review: Mekanisme Antihiperkolesterolemi Kandungan Bawang Putih Tunggal (Allium Sativum Linn) pada Hewan Model - Celine Erditha; Annisa Rahmah Furqaani; Tita Barriah Siddiq (UNISBA Press, 2023)
Abstract. Cardiovascular disease (CVD) is the main cause of death from non-communicable diseases (PTM) in various countries, including Indonesia. Hypercholesterolemia is the main risk factor for CVD. RISKESDAS KEMENKES RI in 2018 noted that 21.2% of Indonesia's population had borderline total cholesterol levels, and 7.6% had high levels. Single garlic (Allium sativum L.), one of Indonesia's biodiversity resources, is known to have a hypolipidemic effect. The high content of bioactive compounds in Allium sativum L., such as flavonoids, saponins, and SAC, plays a major role in reducing blood cholesterol levels. This study aims to determine the effect and mechanism of single garlic bioactive compounds on blood cholesterol levels. Scoping review is the method used, and there are six databases used, namely Proquest, Hindawi, Pubmed, Scopus, Embase, and Garuda. There were 3179 journals with 415 articles that met the inclusion criteria, 4 articles that met the exclusion criteria and PICOS, and 4 articles that met the eligibility criteria. The results of this study showed a decrease in total cholesterol (TC) levels after being given a bioactive compound from the alcoholic extract of Allium sativum L. at various doses, by increasing the activity of antioxidant enzymes and lecithin-cholesterol acyl transferase (LCAT). In conclusion, the single bioactive compound of garlic extract is effective in lowering cholesterol levels through increasing the activity of antioxidant enzymes and LCAT. Abstrak. Cardiovascular disease (CVD) menjadi penyebab kematian utama penyakit tidak menular (PTM) diberbagai negara termasuk Indonesia. Hiperkolesterolemia merupakan faktor risiko utama CVD. RISKESDAS KEMENKES RI tahun 2018 mencatat, 21,2% penduduk Indonesia memiliki kadar kolesterol total borderline dan 7,6% tinggi. Bawang putih tunggal (Allium sativum L.) salah satu keanekaragaman hayati Indonesia yang dikenal memiliki efek hipolipidemik. Tingginya kandungan senyawa bioaktif pada Allium sativum L. seperti flavonoid, saponin dan SAC menjadi pemeran utama dalam menurunkan kadar kolesterol dalam darah. Penelitian ini bertujuan untuk mengetahui pengaruh dan mekanisme kandungan senyawa bioaktif bawang putih tunggal terhadap kadar kolesterol darah. Scoping review menjadi metode yang digunakan, terdapat enam database yang digunakan yaitu Proquest, Hindawi, Pubmed, Scopus, Embase dan Garuda. Terdapat 3179 jurnal dengan 415 artikel yang sesuai dengan kriteria inklusi, 4 artikel yang sesuai dengan kriteria ekslusi dan PICOS serta 4 artikel yang sesuai dengan kriteria kelayakan. Hasil penelitian ini menunjukan adanya penurunan kadar Total Cholesterol (TC) setelah diberikan senyawa bioaktif dari ekstrak alkohol Allium sativum L. dengan berbagai dosis, melalui peningkatan aktivitas enzim antioksidan dan lecithin-cholesterol acyl transferase (LCAT). Simpulan, senyawa bioaktif ekstrak bawang putih tunggal efektif dalam menurunkan kadar kolesterol melalui peningkatan aktivitas enzim antioksidan dan LCAT.